2021
DOI: 10.1016/j.jhydrol.2021.126252
|View full text |Cite
|
Sign up to set email alerts
|

Measuring precipitation in Eastern Himalaya: Ground validation of eleven satellite, model and gauge interpolated gridded products

Abstract: HighlightsGPM-IMERG and WRF are recommended for hydroclimatic applications in Eastern Himalaya ERA5, TRMM-3B42RTV7 and IMD-0.25°captured extreme precipitation events satisfactorily IMD-0.25°is advised for precipitation trend analysis after suitable bias-correction GPPs underestimated (overestimated) precipitation below (above) 3000 masl elevation Satellite GPPs captured the seasonal and diurnal cycles with subdued amplitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 95 publications
3
30
2
1
Order By: Relevance
“…For different precipitation intensities, ERA5 and IMERG showed shortcomings of overestimating weak and underestimating high-intensity precipitation, which has been reported for eastern China 130 , 131 , the Himalayas 132 , North America 35 , and Central Asia 133 . The overestimation of weak precipitation can be explained by reasons for overall overestimation above.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…For different precipitation intensities, ERA5 and IMERG showed shortcomings of overestimating weak and underestimating high-intensity precipitation, which has been reported for eastern China 130 , 131 , the Himalayas 132 , North America 35 , and Central Asia 133 . The overestimation of weak precipitation can be explained by reasons for overall overestimation above.…”
Section: Discussionmentioning
confidence: 71%
“…Specifically, ERA5-HRES is applicable for long-term, large-scale research, such as interdecadal variability and trend analysis, as noted by assessments on the Tibetan Plateau 94 , 123 . With higher spatial resolution and better characterization of daily precipitation, ERA5-Land has great potential for topographic precipitation detection and glacio-hydrological studies, which has also been suggested by a study in mountainous areas 132 . However, IMERG products still show advantages in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…The western section of the North region is mainly distributed in plain areas and near river valleys (with a lower altitude), while the northern section is located in peak gathering area (with a higher altitude), indicating that the three products are also sensitive to the identification of the maximum precipitation altitude zone. For the micro precipitation in high-altitude mountainous areas, although GPM shows a low detection rate for daily precipitation events (Figure 11), the V06 version of IMERG, based on the optimization of the system algorithm and the upgrading of the sensor level, improves the estimation error of the micro precipitation in a long-time scale (month, year) [46,96].…”
Section: Factors Influencing the Accuracy Of Satellite Precipitation ...mentioning
confidence: 99%
“…For example, Wang [44] and Li [45] et al took the Qilian Mountains as the research object. In the study comparing the applicability of the Weather Research and Forecast (WRF) reanalysis products with TRMM and the fifth generation of atmospheric reanalysis by the European Centre for Medium-Range Weather Forecasts (ERA5) [46,47], they found that there are great differences in the estimation of annual and seasonal precipitation in different precipitation datasets at high latitudes; Similar conclusions were reached in the Tianshan Mountains [48]. This illustrates the value of cross-comparisons of datasets to provide in-depth details on the performance of precipitation indicators data important for hydrological and climatic studies.…”
Section: Introductionmentioning
confidence: 99%
“…At catchment scales, most of such studies have come from the Western and Central (Nepal) Himalaya and have focused on establishing linkages between stream characteristics and land-use forms, including the role of TMFs (Sharma et al , 2007;Krishnaswamy, 2017). The region is projected to experience significant warming (0.8-1.2 °C decade -1 ), increasingly drier winters and wetter monsoon and summer seasons trends under climate change (Krishnan et al , 2019;Kumar et al , 2021). Broad-leaved secondary forests form a significant portion (32.5 %) of total area under TMFs in Sikkim and are likely to have distinctly altered carbon and water cycles than primary forests (Kanade and John, 2018;Bhutia et al , 2019).…”
Section: Introductionmentioning
confidence: 99%